A Novel Method for Assessing Lamina Cribrosa Structure Ex Vivo Using Anterior Segment Enhanced Depth Imaging Optical Coherence Tomography. Issue 7 (July 2017) - Chien, Jason L.; Ghassibi, Mark P.; Mahadeshwar, Pooja; Li, Pengcheng; Liebmann, Jeffrey M.; Ritch, Robert; Milman, Tatyana; Park, Sung Chul
Abstract : Purpose: The purpose of this study is to investigate the use of anterior segment enhanced depth imaging (EDI) optical coherence tomography (OCT) for ex vivo lamina cribrosa (LC) imaging. Materials and Methods: After removing anterior segment and vitreous, the optic nerve head (ONH) tissue of porcine eyes was placed on a customized eye holder for imaging. Serial EDI OCT B-scans (interval, ∼35 μm) of the ONH were obtained using anterior segment module of spectral-domain OCT. Various conditions were tested for better quality LC images. After EDI OCT, serial histologic sections were obtained (distance between sections, ∼5 μm). LC structures in OCT scans were compared with those in histologic sections. Three-dimensional LC reconstructions created using serial OCT scans were compared with LC structures in disc photographs. Results: ONHs of 3 enucleated eyes were examined. The LC was more clearly imaged when the retina and part of the prelaminar tissue were removed (quality score, 39.01±3.30 vs. 26.40±5.85; P <0.001) and when the tissue was kept moist during imaging (quality score, 38.70±2.11 vs. 36.18±5.98; P <0.001). LC image quality was similar before and after fixation (quality score, 38.84±6.57 vs. 39.21±9.69; P =0.79). LC beams and part of retrolaminar glial columns identified in OCT scans matched those in histologic sections. LC beams and pores in 3-dimensional reconstructions matched those in disc photographs. Conclusions: High-resolution cross-sectional images of the LC, comparable to histologic sections, can be obtained using anterior segment EDI OCT in ex vivo eyes with proper tissue preparation.